Healthcare expenditure and GDP in Ethiopia from 1995 to 2014: a time-series analysis - Kedir Hussein Abegaz; Abdulnasir Abdulmelike Mohammed (Agriculture & Food Security, 2018)
Abstract Background With an increasing attention from researchers, policymakers, and the priority of healthcare aspects, explaining the relationship between healthcare expenditure (HCE) and gross domestic product (GDP) is of great importance to the academics in particular and government policymakers in general. Thus, this study aimed at investigating whether HCE and GDP have a long-term relationship and at measuring the elasticity of HC from 1995 to 2014. Methods This study used yearly HCE and GDP data of Ethiopia during the period 1995–2014. Line graph was used to visualize the trend. Augmented Dickey–Fuller and Johansen cointegration tests were carried out to check stationarity and the long-run equilibrium relationship between the variables, respectively. We also examined the elasticity of healthcare expenditure using ordinary least squares, least absolute deviations, least mean squares, and M-estimator estimation approach. Results The results confirm that there was a significant long-run relationship between the variables. In addition, the results of this study based on the four estimation approaches show that increasing GDP has a significant and positive impact on healthcare expenditure. The income elasticity of total and government healthcare expenditure was less than one nearly 0.05 and 0.028%, respectively. Conclusions The results of this study, therefore, suggest that HCE and GDP have a long-term cointegration and that health expenditures were a necessity in Ethiopia. This study finally suggests for government in general and Ministry of Health and the Ministry of Finance in specific to continue on their effort to increase healthcare expenditure not only by increasing government expenditure but also by enabling private health expenditure in healthcare coverage.